1884 Iowa Acts 86 - (:unkn) unknown (My University, 1884)
§§ 1-3: Prohibited the sale, present, or giving of any pistol, revolver, or toy pistol to any minor. Violators fined not less than twenty-five nor more than one hundred dollars or imprisonment not less than ten nor more than thirty days.
Keywords: TRANSFER - MINORS